Mouse acidic mammalian chitinase exhibits transglycosylation activity at somatic tissue pH. Issue 20 (30th August 2017) - Wakita, Satoshi; Kobayashi, Shunsuke; Kimura, Masahiro; Kashimura, Akinori; Honda, Shotaro; Sakaguchi, Masayoshi; Sugahara, Yasusato; Kamaya, Minori; Matoska, Vaclav; Bauer, Peter O.; Oyama, Fumitaka
Abstract : Mouse acidic mammalian chitinase (AMCase) degrades chitin with highest efficiency at pH 2.0 and is active up to pH 8.0. Here, we report that mouse AMCase also exhibits transglycosylation activity under neutral conditions. We incubated natural and artificial chitin substrates with mouse AMCase at pH 2.0 or 7.0 and analyzed the resulting oligomers using an improved method of fluorescence‐assisted carbohydrate electrophoresis. Mouse AMCase produces primarily dimers of N ‐acetyl‐d ‐glucosamine [(GlcNAc)2 ] under both pH conditions while generating transglycosylated (GlcNAc)3 primarily at pH 7.0 and at lower levels at pH 2.0. These results indicate that mouse AMCase catalyzes hydrolysis as well as transglycosylation and suggest that this enzyme can play a novel role under physiological conditions in peripheral tissues, such as the lungs. Abstract :